Thiophene and diaminobenzo- (1,2,5-thiadiazol)- based DAD-type near-infrared fluorescent probe for nitric oxide: A theoretical research - Lin, X. Y.; Sun, S. H.; Liu, Y. T.; Shi, Q. Q.; Lv, J. J.; Peng, Y. J. (Frontiers in Chemistry, 2023)
A near-infrared fluorescent probe (LS-NO) for the real-time detection of nitric oxide (NO) in inflammatory bowel disease (IBD) was developed recently. The probe used oligoglycol morpholine functionalized thiophene as strong electron donors and diaminobenzene (1,2, 5-thiadiazole) as weak electron acceptor and NO trapping group. It could detect exogenous and endogenous NO in the lysosomes of living cells with high sensitivity and specificity. To further understand the fluorescent mechanism and character of the probe LS-NO and LS-TZ (after reaction of the probe LS-NO with NO), the electron transfer in the excitation and emitting process within the model molecules DAD-NO and DAD-TZ were analyzed in detail under density functional theory. The calculation results indicated the transform from the diaminobenzene (1,2, 5-thiadiazole) as weak electron acceptor to triazolo-benzo-(1,2,5-thiadiazole) as strong electron acceptor made LS-NO an effective "off-on" near-infrared NO fluorescent probe.